The Effect of Using Mind Mapping to Students’ Reading Comprehension - Gresti Fina Ramadhan; Endah Tri Wisudaningsih; Ririn Fatmawati (Institut Agama Islam Negeri Palopo, 2023)
This research was intended to analyze the effect of mind mapping towards students reading comprehension at twelfth grade in MAN 2 Probolinggo. A lot of students still struggle with reading. To overcome students' challenges, teachers should have tactics when teaching reading comprehension. Using two groups pre- and post-test at an experiment and a control group, this study used the quasi-experimental methodology. The sample classes, which included 17 students in each, were twelfth social 2 and twelfth social 3. Technique for data analysis utilizing the Paired Sample T Test. The alternative hypothesis is rejected if the significance value, or Sig (2-tailed), is more than 0.05. The hypothesis is accepted if the significance value, or Sig (2-tailed), is less than 0.05. According to the findings, students who learnt by using mind map were able to develop at a higher level. If the results of hypothesis testing indicate a Sig value (2-tailed) of 0.000 < 0.05, then the test decision-making methodology is appropriate. It can be inferred from paired Sample T Test that the mind map method affects students' capacity for reading comprehension